2013
DOI: 10.1002/phar.1159
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline‐Related Pancreatitis: A Review of Spontaneous Adverse Event Reports

Abstract: Our analysis suggests a quantitative signal between tigecycline use and pancreatitis; however, given the limitations of our study, a cause-and-effect relationship cannot be inferred. Thus, additional rigorous scientific analyses are warranted to explore these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
(38 reference statements)
3
15
0
4
Order By: Relevance
“…Other antibiotics with MRSA activity such as ceftaroline, ceftobiprole, telavancin, and tigecycline represent alternatives for the treatment of infections caused by drug-resistant Gram-positive pathogens [ 8 ]. However, there are some reports of safety issues associated with these antibiotics; hematological disorders and rash with ceftaroline, gastrointestinal upset with ceftobiprole, nephrotoxicity with telavancin, and pancreatitis with tigecycline [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other antibiotics with MRSA activity such as ceftaroline, ceftobiprole, telavancin, and tigecycline represent alternatives for the treatment of infections caused by drug-resistant Gram-positive pathogens [ 8 ]. However, there are some reports of safety issues associated with these antibiotics; hematological disorders and rash with ceftaroline, gastrointestinal upset with ceftobiprole, nephrotoxicity with telavancin, and pancreatitis with tigecycline [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatitis has been identified in pharmacovigilance databases during post-approval use of tigecycline. 9,11,12 Because these reactions are reported voluntarily from a population of uncertain size, it is not always possible to reliably estimate their frequency or establish causal relationship to drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to both studies, however, include the inability to enforce standardized criteria for drug-induced pancreatitis as well as inability to re-challenge patients with the drug. Thus, cause-and-effect determination was not possible with either review [2,3].…”
Section: Okon Et Al Performed a Review Of The Fda Adverse Eventmentioning
confidence: 92%
“…Reporting System, the results of which revealed an increase in pancreatitis reports (with the 5th percentile of the distribution of the relative reporting ratio [RRR 05 ] of 10.4) [2]. In contrast, a subsequent review of Phase 3 and 4 comparative tigecycline studies by McGovern et al concluded that the incidence of tigecycline-associated pancreatitis did not exceed comparator antibiotics, occurring in less than 1% of all cases of exposure.…”
Section: Okon Et Al Performed a Review Of The Fda Adverse Eventmentioning
confidence: 93%
See 1 more Smart Citation